Gut microbiota modulation by Traditional Chinese Medicine: a translational strategy for metabolic dysfunction-associated steatotic liver disease - Zhou, Ting; Jin, Ziwen; Jiang, Rilei; Li, Weiwei (Frontiers in Pharmacology, 2025)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD) has emerged as a critical global health burden, driven by rising prevalence rates and earlier disease onset. Current therapeutic strategies remain limited to lifestyle interventions, with no approved pharmacotherapies targeting disease progression. Growing evidence highlights gut microbiota dysbiosis as a pivotal contributor to MASLD pathogenesis, characterized by disrupted intestinal barrier function, endotoxin translocation, and dysregulated bile acid (BA) and short-chain fatty acid (SCFA) metabolism. Preclinical studies suggest that specific botanical drugs and standardized polyherbal formulations may mitigate MASLD through microbiota modulation.MethodsA systematic review of preclinical and clinical studies (2015–2025) was conducted across PubMed, Web of Science, and CNKI. Search terms included “gut microbiota,” “Traditional Chinese Medicine (TCM),” and “MASLD,” focusing on studies with chemically defined botanical metabolites (purity >90%) or rigorously characterized polyherbal formulations. Exclusion criteria eliminated reports lacking microbial taxonomic validation (e.g., 16S rRNA sequencing), dose-response relationships, or mechanistic validation in animal models.ResultsThe synthesis of studies reveals that TCM ameliorates MASLD through three interconnected mechanisms: restoration of gut microbial diversity, reinforcement of intestinal barrier integrity via tight junction protein upregulation (e.g., ZO-1 and occludin), and normalization of BA/SCFA metabolism. Among the 10 botanical drugs and 11 formulations reviewed, significant reduction in liver steatosis were shown in rodent models. However, only 4% of these interventions progressed to human trials, and critical methodological inconsistencies were observed, including inconsistent phytochemical standardization and overreliance on homogeneous animal models (68% using male C57BL/6 mice).ConclusionWhile TCM shows promise in modulating microbiota-liver crosstalk, clinical translation is hindered by insufficient phytochemical standardization, unvalidated multi-component synergies, and a paucity of human efficacy data. To bridge this gap, future research must prioritize randomized controlled trials with liver histology endpoints, ConPhyMP-guided quality control protocols, and humanized microbiota models. Rigorous validation of TCM’s microbiota-centric mechanisms—rather than empirical applications—will be essential to advance these interventions into clinically actionable therapies for MASLD.